2022
DOI: 10.3390/ijerph19010568
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Investigation into the Mental Health of Healthcare Workers in Japan during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has negatively impacted the mental health of healthcare workers in many countries including Japan. While many survey-based findings have reported the serious state of their wellbeing among healthcare workers, the first-hand experience of the mental health and coping in this population remains to be evaluated. Accordingly, this study aimed to appraise them using constructionist thematic analysis on semi-structured interviews attended by a purposive and snowball sample of 24 healthcare work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 49 publications
1
45
0
10
Order By: Relevance
“…In addition, management that also encouraged HCWs' self-care may also increase healthy coping and foster resilience within a team; “my line manager believes that if we don't take good care of ourselves, we cannot take care of others. He supports self-care, which positively impacts our workplace culture.” ( Kotera et al, 2022 ). The provision of clear guidance by effective and supportive leaders that is responsive to HCWs' needs served to reduce stress and may be essential in supporting resilience during a pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, management that also encouraged HCWs' self-care may also increase healthy coping and foster resilience within a team; “my line manager believes that if we don't take good care of ourselves, we cannot take care of others. He supports self-care, which positively impacts our workplace culture.” ( Kotera et al, 2022 ). The provision of clear guidance by effective and supportive leaders that is responsive to HCWs' needs served to reduce stress and may be essential in supporting resilience during a pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…A good level of communication is thought to help maintain a higher level of psychological well-being [ 27 ]. An effective coping strategy is vital to maintaining high levels of psychological well-being under extreme conditions [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the results showed that reliable social support at work could be a protective factor against depression, stress, and suicidal ideation, which is consistent with reports that have mentioned the importance of social support and resilience in moderating psychological distress [ 69 ]. Moreover, communicating and connecting with colleagues at the workplace, sharing experiences, giving each other advice [ 70 ], and teamwork [ 71 ] have been reported to improve the mental health of HCWs during the pandemic. Therefore, authorities should implement interventions to enhance work relations and promote peer-to-peer interactions, especially under stressful circumstances.…”
Section: Discussionmentioning
confidence: 99%